Solid state hydrogen storage : materials and chemistry - Walker, G. (Gavin) (Woodhead Publishing in materials., 2008)
Hydrogen fuel cells are emerging as a major alternative energy source in transportation and other applications. Central to the development of the hydrogen economy is safe, efficient and viable storage of hydrogen. Solid-state hydrogen storage: Materials and chemistry reviews the latest developments in solid-state hydrogen storage. Part one discusses hydrogen storage technologies, hydrogen futures, hydrogen containment materials and solid-state hydrogen storage system design. Part two reviews the analysis of hydrogen interactions including structural characterisation of hydride materials, neutron scattering techniques, reliably measuring hydrogen uptake in storage materials and modelling of carbon-based materials for hydrogen storage. Part three analyses physically-bound hydrogen storage with chapters on zeolites, carbon nanostructures and metal-organic framework materials. Part four examines chemically-bound hydrogen storage including intermetallics, magnesium hydride, alanates, borohydrides, imides and amides, multicomponent hydrogen storage systems, organic liquid carriers, indirect hydrogen storage in metal ammines and technological challenges in hydrogen storage. With its distinguished editor and international team of contributors, Solid-state hydrogen storage: Materials and chemistry is a standard reference for researchers and professionals in the field of renewable energy, hydrogen fuel cells and hydrogen storage. Assesses hydrogen fuel cells as a major alternative energy sourceDiscusses hydrogen storage technologies and solid-state hydrogen storage system designExplores the analysis of hydrogen interactions including reliably measuring hydrogen uptake in storage materials.